Short Communication: Population and stand structure of Cinnamomum sintoc in the Low Land Forest of Mount Ciremai National Park, West Java, Indonesia - AGUS YADI ISMAIL; CECEP KUSMANA; EMING SUDIANA; PUDJI WIDODO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Ismail AY, Kusmana C, Sudiana E, Widodo P. 2019. Short Communication: Population and stand structure of Cinnamomum sintoc in the Low Land Forest of Mount Ciremai National Park, West Java, Indonesia. Biodiversitas 20: 1042-1047. Cinnamomum sintoc (C. sintoc) is one of the anthelmintic and anti-inflammatory medicinal plants which produces essential oils from its roots, skin, and leaves. This study aimed to analyze the population and stand structure of C. sintoc in Mount Ciremai National Park, West Java, Indonesia. Data collection was carried out using plots/ strips method. The plots were purposively placed and made at each altitude and direction of the slope. The research recorded 804 individual trees from each growth edge. Individual density between slope directions and altitudes was not significantly different for all diameter classes, but was significantly different between slope directions of stratum B (P = 0.001) and E (P = 0.012). These results indicate that sintoc population is spread evenly and can be cultivated at various slope and altitude directions and has no preference for the two topographic variables.